EXPLORING INFORMATION AND SOLUTIONS IN ARABIC MANUSCRIPTS IN THE MIDDLE OF THE COVID-19 PANDEMIC - Uus Rustiman; Yani Rohmayani; Ade Kosasih (International Journal of Multidisciplinary Research and Literature, 2022)
This study discusses the Badzl al-Mā'un fī Fadhl at-Thā'ūn Manuscript; Exploring Information and Solutions in Arabic Ancient Texts amid the Covid-19 Pandemic. This research not only has scientific (theoretical) use-value for philology but can be utilized by further research. Philological research, in this regard, is more of basic research that is very open to further research steps which are considered far from having practical value. A study of the Badzl al-Mā'un fī Fadhl ath-Thā'ūn Manuscript which means "assisting the sufferers." tho'un disease” is one of the works of Al-Imam Al-Hafidz Ibn Hajar al-'Asqallany (d. 852 H/1448 AD) which is very urgent to do, considering its strategic position as one of the references related to Excavating Information and Solutions in Arabic Ancient Manuscripts amid the Covid-19 Pandemic. Therefore, it is in this central position that the research on this manuscript becomes very important. As a study, this research requires an accurate research format and method of the Badzl al-Mā'un fī Fadhl ath-Thā'ūn Manuscript. This study examines how the Model of Digging for Information and Solutions in Arabic Ancient Texts in the Middle of the Corona Pandemic